Modalitas Deteksi Dini Penyakit Jantung Bawaan di Pelayanan Kesehatan Primer - Eva Miranda Marwali; Yoel Purnama; Poppy Surwianti Roebiono (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Congenital heart disease (CHD) is a disorder both in the structure of the heart or large blood vessels and heart function that is obtained since it is still in the womb and can be a major cause of death in the first year of life. The prevalence of CHD events worldwide reaches 9.4 per 1000 live births including in Indonesia. Of these, around 300,000 cases are categorized as severe CHD which sometimes requires gradual surgery in order to survive. The purpose of this paper is to increase the understanding of the signs and symptoms of CHD by general practitioners with simple modalities that can be used in the initial screening of CHD in peripheral areas. Early detection of CHD in primary health services can be done with history taking, physical examination, and simple modalities such as pulse oximetry, electrocardiography, and chest X-ray. Early detection of CHD is expected to reduce the morbidity and mortality rate of CHD in Indonesia.